Processes of evaluating the service of using motor vehicles - Norkobilov Jahongir Isroil ogli (THE INNOVATION ECONOMY, 2026)
The article highlights the origin and stages of development in evaluating services related to the use of motor vehicles. It analyzes the development of motor vehicles, the quality of services provided to the population, and the effective improvement of vehicle service evaluation to enhance the quality of life. The article also addresses the reliability of evaluation results and the fundamental differences between evaluating vehicle services and other types of object evaluations.